Et Cetera: Tayfun Akgül's scientifc cartoons exhibition during ELECO 2013 - Akgül, Tayfun; Suer, Can (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Since 1999, the Bursa Branch of the Chamber of Electrical Engineers of Turkey, together with Uludag University and Istanbul Technical University, have organized an international conference (the 8th International Conference on Electrical and Electronics Engineering, ELECO) in Bursa, a historical city in Turkey where the Ottoman Empire was established. This year, on October 28?30, 2013, the ELECO conference hosted more than 200 engineers, academicians, and experts in electrical and electronics engineering. It was full of sessions and invited speakers on recent developments in electrical energy, smart-grid applications, electronic circuits, high-frequency micro chip circuits, and new technologies in computer science (Figure 1).